The design of Mn2+&Co2+ co-doped CdTe quantum dot sensitized solar cells with much higher efficiency. Issue 59 (29th September 2020) - Li, Huazheng; Lu, Wangwei; Song, Bin; Zhou, Jing; Zhao, Gaoling; Han, Gaorong
Abstract : Mn 2+ &Co 2+ co-doped CdTe QDs were successfully synthesized via aqueous phase method with mercaptopropanoic acid, which could generate different doping energy levels, and as sensitizers applied for QDSCs, showing a significantly enhanced efficiency. Abstract : High quality Mn 2+ -doped CdTe quantum dots (QDs), Co 2+ -doped CdTe QDs and Mn 2+ &Co 2+ co-doped CdTe QDs were successfully synthesized via an aqueous phase method with mercaptopropanoic acid (MPA) ligands. The doped QDs maintain the same zinc blende structure of CdTe by X-ray diffraction (XRD). The Mn 2+ -doped CdTe QDs and Co 2+ -doped CdTe QDs both show a red-shift on absorption and photoluminescence (PL) spectra compared to pure CdTe QDs. In addition, Mn 2+ -doped CdTe QDs show a significant increase in the PL lifetime due to an orbitally forbidden d–d transition, which is of benefit to the reduction of electron recombination loss. Co 2+ doping has a more matched doping energy level. In view of this, Mn 2+ &Co 2+ co-doped CdTe QDs were applied as sensitizers for quantum dot sensitized solar cells, resulting in a significantly enhanced efficiency.